(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
With advances in wireless technology and digital electronics, several small gadgets have begun to be utilized in a variety of everyday situations. The concept of IoT enables rapid access to environmental data. Efficiency and productivity are drastically increasing in many operations. This paper provides a comprehensive review of WSNs. These gadgets have the ability to sense, compute, and communicate. Low-power radios, a number of smart sensors, and embedded CPUs are common components (Central Processing Units). These devices are used to create a wireless sensor network (WSN), which is required for detecting and monitoring environmental variables. Parallel to WSNs, the concept of the internet of things (IoT) is gaining traction, with IoT being defined as the connectivity of identifiable objects via an internet connection for sensing and monitoring purposes. This article provides a comprehensive review of WSNs. It also evaluates WSNs’ technology and features. In addition, it includes a discussion of WSN and IoT applications.